2002 annual report of the Multilateral Investment Guarantee Agency - The World Bank.; Multilateral Investment Guarantee Agency (Washington D.C. : The World Bank Group, 2002)
This is the 2002 annual report of one of the World Bank institutions, Multilateral Investment Guarantee Agency (MIGA).
osc 16/08/2016
Ref.
Keywords: Banks and banking , International; Investment